Assessment of the feed additive consisting of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) DSM 21762 for all animal species for the renewal of its authorisation (Lactosan GmbH & Co KG) - Bampidis, Vasileios (EFSA J, 2021)
Following a request from the European Commission, the Panel on Additives and Products or Substances used in Animal Feed (FEEDAP) was asked to deliver a scientific opinion on the assessment of the application for renewal of authorisation of Lactiplantibacillus plantarum (formerly Lactobacillus plantarum) DSM 21762, as a technological additive for all animal species. The applicant has provided evidence that the additive currently in the market complies with the existing conditions of authorisation. There was no new evidence that would lead the FEEDAP Panel to reconsider its previous conclusions. Thus, the Panel concluded that the additive remains safe for all animal species, consumer and the environment under the authorised conditions of use. The additive was not irritant to skin and eyes but is considered a skin and respiratory sensitiser. The present application for renewal of the authorisation did not include a proposal for amending or supplementing the conditions of the original authorisation that would have an impact on the efficacy of the additive. Therefore, there was no need for assessing the efficacy of the additive in the context of the renewal of the authorisation.